A novel biocompatible, simvastatin-loaded, bone-targeting lipid nanocarrier for treating osteoporosis more effectively. Issue 35 (28th May 2020) - Tao, Shan; Chen, Shao-qing; Zhou, Wen-tao; Yu, Fang-ying; Bao, Lu; Qiu, Guo-xi; Qiao, Qing; Hu, Fu-qiang; Wang, Jian-wei; Yuan, Hong
Abstract : A scheme of the preparation of SIM/ASP6 -LNPs and a mechanism which indicated that SIM/ASP6 -LNPs could improve the efficacy of SIM on the recovery of osteoporosis under the action of bone-targeting moieties ASP6 . Abstract : An insufficient drug concentration at the target site and drug efflux resulting in poor efficacy are recognized as important obstacles in osteoporosis treatment. Simvastatin (SIM), which can treat osteoporosis by promoting osteoblast differentiation and mineralization through the bone morphogenetic proteins (BMP)-Smad signaling pathway, has lower bioavailability, and less bone tissue distribution. Herein, novel lipid nanoparticles (LNPs) delivering SIM (SIM/LNPs) for osteoporosis therapy were developed with aspartic oligopeptide (ASP n, here ASP6 )-based bone-targeting moieties grafted to the nanoparticles (SIM/ASP6 -LNPs) in an attempt to increase the concentration of SIM in bones with a relatively low dose to minimize adverse effects. In vivo experiments indicated that the ASP6 -LNPs exhibited ideal bone-targeting characteristics, and in vitro cell evaluation experiments showed LNPs have good biocompatibility with MC3T3-E1 cells. The cell mineralization experiment revealed that the SIM-loaded LNPs induced osteoblast differentiation and the formation of mineralized nodules in MC3T3-E1 cells, achieving the same efficacy as that of SIM. Pharmacodynamic experiments revealed that SIM/ASP6 -LNPs improved the efficacy of SIM on the recovery of bone mineral density when compared to SIM/LNPs or to SIM alone. Therefore, SIM/ASP6 -LNPs may represent a potential bone-targeting drug delivery system (DDS) that contributes to the development of a novel osteoporosis treatment.